(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Fiscal rules have been the centre of economic debate in European Union Member States. They indicate the direction in which policymakers aim to evolve public finances. In recent years the public finances of European Union Member States have been affected by two major changes in economic and institutional settings. These are the establishment of Economic and Monetary Union and progressive fiscal decentralisation in a significant number of European Union Member States. In order to support the fiscal decentralisation process European Union Member States need to have appropriate fiscal policy rules. They can stimulate policy coordination between different levels of government depending on their institutional coverage. The aim of this paper is to present an analysis of the fiscal rule index and fiscal rule strength index in European Union Member States, with special emphasis on Croatia. The Directorate-General for Economic and Financial Affairs methodology was used in analysing the fiscal rule index and fiscal rule strength index by type and government sectors in the period from 2003-2013 in European Union Member States. Based on our results, the fiscal rule index for Croatia, from the period 2003-2013, is continually on the rise from -1.01 in 2008 to a high 1.43 in 2013. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.